Structural Equation Modeling of Psychosomatic Complaints Based on Perceived Stress, Anxiety Sensitivity, with the Mediating Role of the Active Activation System in Adolescent Girls - Afrasiabi, Mahnaz; Jomehri, Farhad; Leilabadi, Lida (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: The current research endeavors to forecast psychosomatic complaints among adolescent female students in Tehran by exploring the interplay between perceived stress and anxiety sensitivity, with a particular focus on the mediating role of behavioral activation systems. Methods: The method of the present research was correlation. The statistical population included all female adolescents studying during the academic year 2021-2022 in the high schools of Tehran. The sample size consisted of 620 female students selected through multi-stage cluster sampling. Data were collected using the Takata and Sakata (2004) Psychosomatic Complaints Scale, Cohen’s Perceived Stress Scale (PSS), Garfield and Marcus (2005) Anxiety Sensitivity Index (ASI), and Carver and White’s (1994) Behavioral Activation and Behavioral Inhibition Scales (BAI). Research data were analyzed using SPSS version 25 and PLS version 3.3 software. Results: The results indicated that the direct effect of perceived stress on behavioral activation (β = -0.22, p < 0.05) and psychosomatic complaints is significant (β = 0.49, p < 0.05). The direct effect of anxiety sensitivity on behavioral activation (β = 0.13, p < 0.05) and psychosomatic complaints (β = 0.34, p < 0.05) is also significant. The direct effect of behavioral activation on psychosomatic complaints is significant (β = 0.08, p < 0.05). The indirect effect of perceived stress through the mediating role of behavioral activation on psychosomatic complaints is significant. Conclusions: The findings indicate that the proposed model exhibits a strong fit and represents a pivotal advancement in understanding the factors influencing psychosomatic complaints in adolescent girls. In light of these results, it is advisable for clinical psychologists and school counselors to implement targeted interventions focused on reducing anxiety sensitivity and perceived stress. By addressing these factors, practitioners can potentially alleviate psychosomatic issues in adolescent girls, contributing to their overall well-being and mental health.